Potential probiotic Pichia kudriavzevii strains and their ability to enhance folate content of traditional cereal-based African fermented food. (April 2017) - Greppi, Anna; Saubade, Fabien; Botta, Cristian; Humblot, Christèle; Guyot, Jean-Pierre; Cocolin, Luca
Abstract: With the aim of selecting starter cultures with interesting probiotic potential and with the ability to produce folate in a food matrix, yeast strains isolated from fermented cereal-based African foods were investigated. A total of 93 yeast strains were screened for their tolerance to pH 2 and 0.3% of bile salts. Pichia kudriavzevii isolates gave the best results. Selected P. kudriavzevii strains were tested for survival to the simulated human digestion and for adhesion to Caco-2 cells. Moreover, presence of folate biosynthesis genes was verified and production of extra and intra-cellular folate determined during growth in culture medium. 31% of yeast strains could tolerate pH 2, while 99% bile salts. Survival rate after simulated digestion ranged between 11 and 45%, while adhesion rate between 12 and 40%. Folate production was mainly intracellular, maximum after 24 h of growth. To be closer to traditional cereal-based fermentations, a P. kudriavzevii strain with good probiotic potential was co-inoculated with Lactobacillus fermentum strains in a pearl millet gruel. This resulted in in situ folate production that peaked after 4 h. The use of strains with both probiotic and nutritional enrichment properties may have a greater impact for the consumers. Highlights: One Pichia kudriavzevii strain with good probiotic potential was selected in vitro . Selected strains increase folate content of pearl millet fermented gruel in situ . Yeast folate production in vitro was mainly intracellular, max at 24 h. Yeast adhesion rate on Caco-2 cells varied between 12 and 40%. Survival rate after simulated in vitro human digestion ranged between 11 and 45%.